English Historical Linguistics. Volume 1 : an International Handbook. - Bergs, Alexander (Handbücher zur Sprach- und Kommunikationswissenschaft / Handbooks of Linguistics and Communication Science., 2012)
The handbook Historical Linguistics of English offers in more than 130 articles in two volumes a comprehensive, interdisciplinary and theory neutral overview of all central aspects of the history of English. The first volume contains detailed descriptions of the individual linguistic levels, from phonology to syntax, semantics and pragmatics, for each period of the language, from Old English to Late Modern English. Moreover, the volume offers chapters on particular topics pertaining to individual periods such as the 'Great Vowel Shift', standardization, and do-periphrasis. The second volume ta.